Cyanobacteria and Algae Meet at the Limits of Their Habitat Ranges in Moderately Acidic Hot Springs. Issue 1 (27th December 2021) - Fecteau, Kristopher M.; Boyd, Eric S.; Lindsay, Melody R.; Amenabar, Maximiliano J.; Robinson, Kirtland J.; Debes, R. Vincent; Shock, Everett L.
Abstract: Microbial oxygenic photosynthesis in thermal habitats is thought to be performed by Bacteria in circumneutral to alkaline systems (pH > 6) and by Eukarya in acidic systems (pH < 3), yet the predominant oxygenic phototrophs in thermal environments with pH values intermediate to these extremes have received little attention. Sequencing of 16S and 18S rRNA genes was performed on samples from twelve hot springs in Yellowstone National Park (Wyoming, USA) with pH values from 3.0 to 5.5, revealing that Cyanobacteria of the genus Chlorogloeopsis and algae of the genus Cyanidioschyzon (phylum Rhodophyta) coexisted in ten of these springs. Cyanobacterial 16S rRNA genes were more abundant than rhodophyte 18S rRNA genes by 1–7 orders of magnitude, with rhodophyte template abundance approaching that of Cyanobacteria only at the most acidic sites. The ketocarotenoids echinenone and canthaxanthin were identified in samples from all but one spring yielding cyanobacterial sequences and are attributed to pigment synthesis by Cyanobacteria, whereas the absence of detectable chloroplast sequences affiliated with Cyanidioschyzon, pH and temperatures in excess of its limits for growth, and other observations collectively suggested these algae were inactive in many of the springs at the time of sampling. Fluctuations in the supply of meteoric water likely contribute to physicochemical variability in these springs, leading to transitions in microbial community composition. Spatial overlap, but perhaps not temporal overlap, in the habitat ranges of bacterial and eukaryal oxygenic phototrophs indicates that the notion of a sharp transition between these lineages with respect to pH is unwarranted. Plain Language Summary: Photosynthesis evolved in the Bacteria and was transferred to the Eukarya. Oxygenic phototrophs from each domain have different habitat ranges with respect to temperature and pH, the limits of which may be reached in geothermal environments. Cyanobacteria are thought to be excluded from acidic hot spring environments where algae are the dominant oxygenic phototrophs, whereas Cyanobacteria are predominant in neutral to basic hot spring environments. We characterized oxygenic phototrophs in Yellowstone hot springs with intermediate pH values (3–6). Cyanobacteria and algae coexisted in ten of the twelve hot springs studied, but Cyanobacteria were more abundant by 1–7 orders of magnitude. Observations including photosynthetic carbon uptake, pigment (carotenoid and chlorophyll) distributions, and culturing collectively suggested that algae were inactive in these hot springs at the time of sampling in the summer. These hot spring waters are derived from rainwater and snowmelt, with inputs of gases from the hydrothermal system leading to their moderately acidic pH and moderate temperatures. As a result, the springs are chemically dilute and susceptible to changes in pH and temperature caused by fluctuations in fluid supplies that may lead to the springs crossing habitat range boundaries of Cyanobacteria or algae on seasonal or other timescales. Key Points: Gene sequences affiliated with Cyanobacteria and sequences affiliated with algae were both identified in ten moderately acidic hot springs Cyanobacterial sequences were much more abundant than algal sequences, and algae appeared to be inactive in most of the springs when sampled The springs are derived from meteoric water and are prone to changes in pH and temperature that affect the activity of microbial populations